Implementation of Marker Image Based Tracking Dental Care and Tooth Type "GG-Q" Based on Augmented Reality - Markarius Paso; Reza Andrea; Suswanto Suswanto (TEPIAN, 2020)
Augmented Reality (AR) is a technology that allows people to visualize the virtual world as part of the real world. In simple terms AR can be defined as a real environment that is added with virtual objects, this is made possible through certain input devices. Learning media is a tool used in supporting the implementation of the teaching and learning process. In this process, it can be carried out using books or media electronics. One of them is using electronic media in the form of smart phones. In implementing it is applied to the treatment and type of teeth. The types of teeth used are incisors, canines, molars and molars . There are also cavities, tooth structure and dental care . The method used in this research is Marker based tracking. Marker based tracking is a type of Augmented Reality that recognizes a marker and identifies it to add a virtual object to the real environment.